(untitled) (International Journal of Engineering and Computer Science, 2017)
Authentication methods are used to tackle a very important issue, the cyber security. It helps to avoid the illegal use or misuse of highly sensitive data. Completely Automated Public Turing Test to Tell Computer and the Humans Apart (CAPTCHA) is the automatic security mechanism which is used to determine whether the user is a human or the robot. It is a program which generates and grades the tests that are human solvable but is beyond the current computer program capability. Unfortunately among several CAPTCHA techniques, the text catpcha can be easily hacked and are not reliable for the data security. Though CAPTCHA’s that are robust such as complex image CAPTCHA, graphical CAPTCHA, iCAPTCHA are available, yet most of the websites do not implement as they have to rely on the 3rd party CAPTCHA service provider and also due to the fact that the size occupancy which loads their database on the server which is of less size and cause slow operation of the website. This paper describes the various categories of the CAPTCHA systems, their applications and the drawbacks of each CAPTCHA techniques.